2015
DOI: 10.1080/19420862.2015.1086854
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of TTAC-0001, a fully human anti-vascular endothelial growth factor receptor 2 (VEGFR-2/KDR) monoclonal antibody, is associated with inhibition of tumor angiogenesis

Abstract: Vascular endothelial growth factor (VEGF) and its receptors are considered the primary cause of tumor-induced angiogenesis. Specifically, VEGFR-2/kinase insert domain receptor (KDR) is part of the major signaling pathway that plays a significant role in tumor angiogenesis, which is associated with the development of various types of tumor and metastasis. In particular, KDR is involved in tumor angiogenesis as well as cancer cell growth and survival. In this study, we evaluated the therapeutic potential of TTAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Ahani et al reported that the nanobody carried by lentiviral vectors targeting the KDR could potentially reduce the neovascularization in tumor vasculature (22). Other authors have also reported various approaches to inhibit the biological activity of KDR thus resulting in the inhibition of angiogenesis (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Ahani et al reported that the nanobody carried by lentiviral vectors targeting the KDR could potentially reduce the neovascularization in tumor vasculature (22). Other authors have also reported various approaches to inhibit the biological activity of KDR thus resulting in the inhibition of angiogenesis (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no major toxic adverse events were noted in mice treated with angelicin. Angiogenesis is essential for the establishment of the necessary oxygen and nutrient supply to solid tumors, and thus promotes tumor growth and metastasis ( 32 ). To investigate whether the mechanisms underlying the antitumor effects of angelicin involved the inhibition of angiogenetic processes, the expression of p-VEGFR2, a marker of cancer-associated angiogenesis, was assessed using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…KDR exerts the major role in VEGF induced angiogenesis and vascular permeability [ 21 ]. KDR antibody can singlehandedly inhibit the pathological angiogenesis induced by VEGF through inhibition of the KDR downstream tyrosine kinase signal transduction system [ 22 ]. In receptor tyrosine kinase signal transduction system, the survival of vascular endothelial cell after proliferation and differentiation mainly depends on PI3K-Akt that is an important transduction pathway of survival signal; it participates in the angiogenesis-associated signaling pathway like VEGF-mediated endothelium signal transduction: PI3K and upstream VEGFR-2 (KDR) form compound and activate, generate second messenger, activate phosphoinositide dependent protein kinase (PDK), and activate the downstream serine-threonine protein kinase (Akt), and then generate the effect of vascular endothelial cell activation, so the level of activated Akt [which also is phosphorylated Akt (pAkt)] is the important index that represents the activity of PI3K-Akt [ 23 ].…”
Section: Discussionmentioning
confidence: 99%